2020
DOI: 10.15171/jlms.2020.07
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Level Laser, Hard Occlusal Appliance and Conventional Pharmacotherapy in the Management of Myofascial Pain Dysfunction Syndrome; A Preliminary Study

Abstract: Introduction: Myofascial pain dysfunction syndrome (MPDS) is a common temporomandibular joint disorder. Due to its multifactorial etiology, treatment usually involves more than one modality to obtain complementary results. The purpose of this study was to compare the combined effect of a low-level laser, a hard occlusal appliance, and conventional pharmacotherapy with pharmacotherapy only in the management of patients with MPDS. Methods: In this study, 15 patients with MPDS were diagnosed and randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…The ROB assessment was performed for a total of 8[ 10 29 31 32 33 34 35 36 ] studies. Five[ 29 31 32 33 34 ] of the 8 studies described suitable random sequence generation methods, and 2[ 32 33 ] studies reported low-risk allocation concealment methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ROB assessment was performed for a total of 8[ 10 29 31 32 33 34 35 36 ] studies. Five[ 29 31 32 33 34 ] of the 8 studies described suitable random sequence generation methods, and 2[ 32 33 ] studies reported low-risk allocation concealment methods.…”
Section: Resultsmentioning
confidence: 99%
“…(Two studies[ 33 35 ] did not report the number of subjects of each sex.) The main anatomical sites assessed in the 6 studies reporting the results for each sex[ 10 29 32 34 35 36 ] included the masseter muscles and the temporalis muscles (Table 1 ). The laser treatment parameters of each study are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of the current phase was to compare the short-term effect of LLLT to soft occlusive splints on muscular activity in cases of TMD. The effect of conservative measures in treatment of TMD is controversial across literature, whereas moderate to very low-quality evidence regarding the effectiveness of occlusal splint therapy in the treatment of TMD was reported [46,47], equivalent with other therapeutic modalities [43,48,49] or with no effect reported [50].…”
Section: Discussionmentioning
confidence: 99%